2020
DOI: 10.3390/nano10050959
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Study of the Mechanical Response of Diatom Frustules

Abstract: Diatom frustules, with their hierarchical three-dimensional patterned silica structures at nano to micrometer dimensions, can be a paragon for the design of lightweight structural materials. However, the mechanical properties of frustules, especially the species with pennate symmetry, have not been studied systematically. A novel approach combining in situ micro-indentation and high-resolution X-ray computed tomography (XCT)-based finite element analysis (FEA) at the identical sample is developed and applied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…This group has been extensively studied by researchers since the 18th century because of its unique and complicatedly patterned frustules (silica cell walls). The mechanical structure of frustules was well investigated, revealing interesting characterizations and patterns [17][18][19]. Interestingly, the frustule is mainly composed of chitin [20] in biogenic silica, which is different than other chitin-based algae [1,21] in nature.…”
Section: Benefits Of Didymomentioning
confidence: 99%
See 1 more Smart Citation
“…This group has been extensively studied by researchers since the 18th century because of its unique and complicatedly patterned frustules (silica cell walls). The mechanical structure of frustules was well investigated, revealing interesting characterizations and patterns [17][18][19]. Interestingly, the frustule is mainly composed of chitin [20] in biogenic silica, which is different than other chitin-based algae [1,21] in nature.…”
Section: Benefits Of Didymomentioning
confidence: 99%
“…Interestingly, the frustule is mainly composed of chitin [20] in biogenic silica, which is different than other chitin-based algae [1,21] in nature. Because of their unique mechanical properties, they have a large variety of applications, such as in the modeling of mechanical properties [19,22], drug delivery [23,24], electronics [25], the modifier of resin [26], and biomimetics [27].…”
Section: Benefits Of Didymomentioning
confidence: 99%
“…However, because the size of most diatom species ranges from 3 µm to 200 µm [ 26 ], traditional mechanical test methods struggle to characterize individual frustules. Recently, new approaches on micro- and nanomechanical tests have been developed and used to study the mechanical behavior of frustules [ 20 , 27 , 28 , 29 ]. Indentation by atomic force microscopy (AFM) on pennate and centric diatoms showed that the elastic modulus varied from several to hundreds GPa depending on the test locations [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indentation by atomic force microscopy (AFM) on pennate and centric diatoms showed that the elastic modulus varied from several to hundreds GPa depending on the test locations [ 27 , 28 ]. In situ microindentation, in combination with scanning electron microscopy (SEM) on pennate diatom frustules ( Didymosphenia geminata ), shows that the applied load to achieve elastic deformation on the epivalve surface ranges from 100 µN to 1000 µN [ 29 ]. In three-point bending experiments on the centric diatom ( Coscinodiscus sp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation